Cell viability of microencapsulated Bifidobacterium animalis subsp. lactis under freeze-drying, storage and gastrointestinal tract simulation conditions - Shamekhi, Fatemeh; Shuhaimi, Mustafa; Ariff, Arbakariya; Manap, Yazid A (Folia microbiologica, 2013)
The purpose of this study was to improve the survival of Bifidobacterium animalis subsp. lactis 10140 during freeze-drying process by microencapsulation, using a special pediatric prebiotics mixture (galactooligosaccharides and fructooligosaccharides). Probiotic microorganisms were encapsulated with a coat combination of prebiotics-calcium-alginate prior to freeze-drying. Both encapsulated and free cells were then freeze-dried in their optimized combinations of skim milk and prebiotics. Response surface methodology (RSM) was used to produce a coating combination as well as drying medium with the highest cell viability during freeze-drying. The optimum encapsulation composition was found to be 2.1 % Na-alginate, 2.9 % prebiotic, and 21.7 % glycerol. Maximum survival predicted by the model was 81.2 %. No significant (p > 0.05) difference between the predicted and experimental values verified the adequacy of final reduced models. The protection ability of encapsulation was then examined over 120 days of storage at 4 and 25 °C and exposure to a sequential model of infantile GIT conditions including both gastric conditions (pH 3.0 and 4.0, 90 min, 37 °C) and intestinal conditions (pH 7.5, 5 h, 37 °C). Significantly improved cell viability showed that microencapsulation of B. lactis 10140 with the prebiotics was successful in producing a stable symbiotic powdery nutraceutical.
Keywords: Infant; Humans; náhražky mateřského mléka; kojenec; Temperature; mikrobiální viabilita; teplota; lyofilizace; Time Factors; lidé; Colony Count, Microbial; Microbial Viability; časové faktory; skladování léků; počet mikrobiálních kolonií; Drug Compounding; příprava léků; probiotika; Drug Storage; Infant Formula; Bifidobacterium; Gastrointestinal Tract; Probiotics; Freeze Drying; gastrointestinální trakt